INFLUENCE QUALITY OF WORK LIFE TO PERFORMANCE EMPLOYEE WITH ORGANIZATIONAL COMMITMENT AND WORK SATISFACTION AS AN INTERVENING VARIABLE AT THE SOCIAL LABOR AND TRANSMIGRATION SERVICES - Winarno Winarno; Sri Dwi Ari Ambarwati; Yanita Primadani (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2023)
The results of the evaluation of the State Organization of the Republic of Indonesia and the Accountability System of Government Agencies, the strengthening of Bureaucratic Reform by the Kemenpan-RB in the field of social welfare, the social performance of the Yogyakarta City Dinsosnakertrans 3 years in a row is very volatile and has never reached the target of 100 points. The purpose of this study was to determine whether or not there is a direct effect of the quality of work life on the performance of Dinsosnakertrans employees, and to determine the indirect effect of the quality of work life (QWL) on employee performance through organizational commitment and job satisfaction. The research method used is quantitative method. The sample size is calculated using the Non-probability technique (saturated sample), and a sample of 68 employees is obtained. The analytical technique used is descriptive analysis, which aims to describe the demographic data of the respondents, and quantitative analysis using Simple Regression Analysis to see the direct effect, and Path Analysis for the mediated indirect effect. The results showed that QWL directly had a positive and significant effect on employee performance. QWL indirectly has no significant effect on employee performance variables through organizational commitment. QWL indirectly, has no significant effect on employee performance variables through employee satisfaction.